Potential of social practice - G. . Nikitina (Высшее образование в России)
The article discusses the question concerning the search of innovative means for preparation of future teachers for social interaction. Тhe students’ social practice is considered as one of such means. It should be based on students’ interaction with social and educational organizations and institutions and should include the elements of social design technology. The potential of social practice for students training for professional and pedagogical activity is defined.